2016
DOI: 10.1002/anie.201603785
|View full text |Cite
|
Sign up to set email alerts
|

Pinpointing a Mechanistic Switch Between Ketoreduction and “Ene” Reduction in Short‐Chain Dehydrogenases/Reductases

Abstract: Three enzymes of the Mentha essential oil biosynthetic pathway are highly homologous, namely the ketoreductases (−)‐menthone:(−)‐menthol reductase and (−)‐menthone:(+)‐neomenthol reductase, and the “ene” reductase isopiperitenone reductase. We identified a rare catalytic residue substitution in the last two, and performed comparative crystal structure analyses and residue‐swapping mutagenesis to investigate whether this determines the reaction outcome. The result was a complete loss of native activity and a sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 17 publications
1
16
0
4
Order By: Relevance
“…With the latter activity being engineered, our work has revealed that the catalytic scope of SDR enzymes can be manipulated, which is in line with the results by Lygidakis et al. concerning C=O and enone reduction . Moreover, our results show that the starting activity is not a prerequisite for obtaining a desired novel functionality, here imine reduction.…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…With the latter activity being engineered, our work has revealed that the catalytic scope of SDR enzymes can be manipulated, which is in line with the results by Lygidakis et al. concerning C=O and enone reduction . Moreover, our results show that the starting activity is not a prerequisite for obtaining a desired novel functionality, here imine reduction.…”
Section: Methodssupporting
confidence: 90%
“…Notably, Lygidakis et al. used protein engineering to address the catalytic scope of SDRs: the exchange of a single residue enabled the switch from C=C (enone) to C=O reduction in SDRs from Mentha piperita …”
Section: Methodsmentioning
confidence: 99%
“…To understand the mechanism of VAS better, the crystal structure was solved (Table and Figure ; PDB ID: 5O98). It closely resembles the structure of salutaridine reductase from Papaver somniferum (SalR; PDB ID: 3O26; i.e., the molecular replacement template) and the recently determined structures of two SDRs from Mentha piperita : menthone‐neomenthol reductase (MNMR; e.g., PDB ID: 5L53) and isopiperitenone reductase (IPR; e.g., PDB ID: 5LCX; Figure S10). Crystallization of VAS was carried out with and without the oxidized cofactor NADP + .…”
Section: Resultsmentioning
confidence: 99%
“…The ER isopiperitenone reductase (IPR) catalyses the C=C reduction of isopiperitenone to cis -isopulegone, while ketoreductases (—)-menthone:(—)-menthol reductase (MMR) and (—)-menthone:(+)-neomenthol reductase (MNMR) reduce menthone and isomenthone to menthol isomers (Scheme 11). 20 The identification of a catalytic residue substitution (IPR E238 to MNMR Y244) followed by residue-swapping mutagenesis and X-ray structure determination suggested this change was a likely cause of the switch from ene-reduction to ketoreduction, respectively.…”
Section: Mechanistic Insightsmentioning
confidence: 99%